2013
DOI: 10.1063/1.4827180
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional nonlinear frequency-mixing photo-acoustic imaging of a crack and observation of crack phantoms

Abstract: A two-dimensional imaging of a crack by nonlinear frequency-mixing photo-acoustic method is reported. The imaging contrast is due to nonlinear photo-thermo-acoustic processes taking place in case of simultaneous excitation by lasers of thermo-elastic and acoustic waves in the vicinity of the cracks. The images are obtained by scanning of two co-focused laser beams in region of crack location. The first cw laser beam, modulated in intensity at low frequency f L , generates a thermoelastic wave, which is able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We hypothesize that the irreversible processes that cause the modification of the quasi-equilibrium state of the crack revealed by the measurements of ''tR(cool)'' and ''tL-R(cool)'' signal amplitudes presented in Figure 4(a) are the processes of asperities destruction on the crack surfaces. Several studies have demonstrated that a crack can be closed with the thermoelastic stress induced by the absorption of intensity-modulated [61][62][63][64] or quasicontinuous laser irradiation. 66,67 Moreover, the AFM topography of a similar crack surface (see Figure 7 in the previous publication) 67 reported earlier, which was obtained by the destruction of a similar sample, revealed asperities of different heights on the crack faces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesize that the irreversible processes that cause the modification of the quasi-equilibrium state of the crack revealed by the measurements of ''tR(cool)'' and ''tL-R(cool)'' signal amplitudes presented in Figure 4(a) are the processes of asperities destruction on the crack surfaces. Several studies have demonstrated that a crack can be closed with the thermoelastic stress induced by the absorption of intensity-modulated [61][62][63][64] or quasicontinuous laser irradiation. 66,67 Moreover, the AFM topography of a similar crack surface (see Figure 7 in the previous publication) 67 reported earlier, which was obtained by the destruction of a similar sample, revealed asperities of different heights on the crack faces.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was later advanced by applying the laser radiation not only for crack modulation but also for generation of ultrasound. The frequency-mixed components of the spectrum are detected by in-contact accelerometers [60][61][62][63][64] and contactless optical techniques, such as interferometry and beam deflection. 61 Furthermore, the contrast of photoacoustic imaging of cracks is improved because of the strong dependence of optoacoustic conversion efficiency on the state of the crack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the LUT provides not only possibilities for both wide-band and narrow-band generation, but also for multi-wave-mode generation. In addition, different modes of waves can carry physical information with special directivity patterns [14] , [15] , [16] , relating to the location of surface cracks, thickness of the specimen, and internal defects [17] , [18] , [19] . The LUT also has a high spatial resolution [20] , which is important for detecting and imaging tiny defects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the invention of semiconductor and laser technology in the early 1960s has allowed it to become one of the most advanced imaging techniques available today (Ganguly & Rao, 1981;Luscher et al, 1984;Ni, 2014). Several researchers have reported that applying photoacoustic measurement to detect material cracking yielded satisfactory results (Chigarev et al, 2009;Yan et al, 2012;Mezil et al, 2013;Setiawan et al, 2017). However, they encountered problems due to the high cost and lack of compactness of this technique (Maslov & Wang, 2008;LeBoulluec et al, 2013;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%